Counterattack tactics with side movements in boxing - Romashov, A. A.; Malkov, O. B.; Zvezdova, A. O. (Theory and Practice of Physical Culture, 2019)
Tactical benefits of a range of side steps are sport-specific in the array of modern martial arts. The side shuffle footwork in modern boxing is mostly defensive and intended to partially support the dynamic attacks and counterattacks. Side movements are generally senseless in the situations when the opponent keeps punching from distance and keeps the range by retreats to avoid a close fight. Side shuffle steps are basically designed to complicate focusing for the opponent and attain different attack line distraction related tactical goals. Multiple side/ diagonal moves are also intended to imbalance and disharmonize the opponents` favorite combat patterns, complicate the range-finding and punching in the encounter, and disrupt the opponents` attacks and footwork on the whole. When the immediate tactical goals are attained as required by the own fight plan and tactics, the side shuffles may significantly contribute to success of the counterattacks. The article overviews and summarized the tactics, logics and mechanisms of the side stepping counterattacks in modern boxing.